Layanan Konseling Trauma Pasca Banjir Bandang Bagi Pengungsi Di Aceh Tamiang: Pendekatan Cognitive Behavioral Therapy (CBT) - Nurul Adela; Neviyarnis N; Yarmis Syukur (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Indonesia is highly susceptible to disasters, with floods frequently triggering Post-Traumatic Stress Disorder (PTSD), anxiety, and depression. This study reviews the effectiveness and implementation of Cognitive Behavioral Therapy (CBT) as a psychological intervention solution post-disaster, utilizing a literature review method. Findings confirm that CBT is significantly effective in reducing anxiety and stress and enhancing resilience (p-value = 0.000). CBT works by modifying cognitions (distorted negative thoughts) and maladaptive behaviors, teaching clients to identify the cognitive errors that instigate psychological disorders. CBT implementation varies (e.g., eight structured sessions) but fundamentally aims to alter thought and behavioral patterns. Therefore, CBT is a vital and appropriate approach for the psychological recovery of disaster victims, assisting them in achieving normal functioning.